2012
DOI: 10.1007/s00402-012-1638-9
|View full text |Cite
|
Sign up to set email alerts
|

Cannulated screw unraveling: a case series and literature-based review of an under-recognized complication

Abstract: Partially threaded cannulated screws have enhanced the orthopedic surgeon's ability to fix periarticular fractures. There are many reports of complications and hardware failure during screw removal, but those during fracture fixation are under-reported and under-recognized in the literature. We describe a 21-year-old healthy man with a grade 1 open displaced medial epicondylar humerus fracture. Upon fracture fixation in the OR using a partially threaded cannulated screw over a Kirschner wire, the threads of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Partially threaded, cannulated cancellous screws are applicable in a variety of fracture patterns but appear to have an increasingly reported mechanical fault. There have been previous reports of the screw unwinding with insertion through dense cortical bone in young patients but our case occurred in an older patient through cancellous bone [1,2] .…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Partially threaded, cannulated cancellous screws are applicable in a variety of fracture patterns but appear to have an increasingly reported mechanical fault. There have been previous reports of the screw unwinding with insertion through dense cortical bone in young patients but our case occurred in an older patient through cancellous bone [1,2] .…”
Section: Introductionmentioning
confidence: 70%
“…The study by Kupperman et al revealed that this complication occurred in young males with dense bone in either the humerus, tibia or cuneiform. It was reported that 75% of cases documented no change in resistance when inserting the screw, only 50% of the defective screws were successfully removed and 25% of screws were left in without attempted removal 2 . Our case is unique in that our patient was elderly and it involved cancellous bone in the scapula.…”
Section: Discussionmentioning
confidence: 99%
“…Kupperman et al 9 have previously summarized 8 cases of cannulated screw unraveling, including 7 cases in 5 previously published studies and 1 single case from their own institution. These cases were of majority male patients (7/8; 88%), included a range of patient ages from 12 to 38 years, as well as involved multiple anatomic locations, including the proximal and distal humerus, proximal and distal tibia and the medial cuneiform.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Furthermore, isolated case reports have described a unique complication in the form of thread failure with screw unraveling. 4 9 …”
mentioning
confidence: 99%
“…Our technique does not need the use of screws for soft-tissue fixation and does not include harvesting and use of tendon grafts, differently from other techniques, avoiding all the related complications. 9,10 It also enables a reconstruction as anatomic and minimally invasive as possible; this allows patients to have a rapid recovery, and they are able to return as soon as possible to the activities of daily living. 11 Moreover, an arthroscopic approach allows the surgeon to identify and treat minor injuries, such as a lesion of the articular portion of the radial collateral ligament or the annular drive-through, that would not be identifiable with an open procedure.…”
Section: Discussionmentioning
confidence: 99%